Prognosis of renal cell carcinoma with bone metastases: Experience from a large cancer centre. (January 2019) - Ruatta, F.; Derosa, L.; Escudier, B.; Colomba, E.; Guida, A.; Baciarello, G.; Loriot, Y.; Fizazi, K.; Albiges, L.
Abstract: Background: Bone metastases (BMs) are associated with significant morbidity and shorter survival in renal cell carcinoma (RCC). Our purpose was to identify prognostic factors for overall survival (OS) in RCC patients with BMs. Methods: Data from patients with BMs from RCC treated at Gustave Roussy between April 1992 and March 2016 were retrospectively collected. Age, sex, Eastern Cooperative Oncology Group-Performance Status, Memorial Sloan-Kettering Cancer Center (MSKCC) risk groups, histology, number and site of bone lesions, concomitant metastases (presence and sites), therapy for BMs (radical resection or palliative surgery, radiotherapy and other local and systemic treatments) and time from diagnosis to BMs were analysed. Synchronous solitary bone metastasis (SSBM) was defined as a single BM without concomitant visceral lesions at the initial diagnosis of RCC. OS was calculated from the date of BMs diagnosis to death or last follow-up using Kaplan–Maier method and modelled with Cox regression analysis. Results: From 1750 patients with diagnosis of RCC followed at Gustave Roussy Cancer Campus, 300 patients with BMs were identified. Median time from diagnosis to BMs was 32.4 months (range 0–324 months). In 64 patients (21%), bone was the only metastatic site, and 22 patients (7%) had an SSBM and 236 patients (79%) had concomitant metastases in other sites. Median OS was 23.2 months (95% confidence interval 19.9–26.2). SSBM patients had better OS than those with concomitant metastases (40 vs 20 months; P < 0.001). At multivariate analysis, concomitant metastases remained predictor of poor prognosis, while MSKCC risk group, radical resection and SSBM were predictors of better OS. Conclusions: This study suggests that MSKCC score, numbers of BMs and radical resection are important prognostic factors for RCC patients with BMs. Additionally, in the presence of solitary BM without concomitant metastases at the initial diagnosis of RCC, bone surgery should be considered to achieve local tumour control and likely increase OS. Highlights: Renal cell carcinoma (RCC) accounts for 3% of all cancers and commonly occurs in Western countries. Most common metastases in RCC occurs to lung, followed by bone involvement in 20–35%, lymph nodes and liver. Bone metastases are very destructive in RCC patients, leading to mainly osteolytic lesions that compromise bone integrity. Skeletal involvement is associated with skeletal-related events, which may require surgical intervention and other therapy. The presence of bone metastases in RCC has negative impact on progression free survival and overall survival of patients.